Systemic delivery of calcium channel blockers for hypertension through transdermal delivery - a review - Mahmood, Syed; AL-japairai, Khater Ahmed Saeed (Trans Tech Publications Ltd, 2021)
Hypertension is a significant public health challenge, responsible for a substantial proportion of deathsand disability globally. Calcium Channel Blockers (CCBs) are an important class for the treatment ofhypertension. However, most of CCBs must be taken more than once daily due to their low oralbioavailability and short half-lives leading to poor patient compliance. There is a growing need forenhancing drug delivery of CCBs to overcome the issues associated with their conventional dosageforms. The administration of the drug through the skin for systemic delivery has been recognized asone of the potential routes in hypertension treatment, especially when drugs suffer from lowbioavailability, short half-life, and undesirable side effects following oral administration. The mainlimitation of transdermal drug delivery is the resistance barrier of skin layers to penetrant molecules.Remarkable research efforts have been made worldwide to minimize the skin barrier and to createtransdermal systems of several CCBs via employing skin-enhancing potential. The persistent progressin this field is promising for development the transdermal dosage forms advance technology in the long term and being commercialized sooner rather than later. This review explores the investigations on the viability and applicability of systemic delivery of numerous CCBs through the skin